2016
DOI: 10.1177/1077801216647797
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Forced Sex and Severe Mental Health, Substance Use, and HIV Risk Behaviors Among Asian American Women

Abstract: We examined the association between forced sex history and mental health, sexual health, and substance use among Asian American women (n = 720); 14.3% of our sample (n = 103) reported forced sex experiences. Multiple logistic regression analyses revealed that participants with forced sex histories were 2-8 times more likely to have higher rates of mental health problems, HIV risk behavior, and substance use. Qualitative analysis was used to supplement the quantitative results and give depth to our findings. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
2
23
1
6
Order By: Relevance
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
“…Intimate partner sexual violence (IPSV) is grave in nature, and it can cause several mental and/or physical health problems or disabilities. Researchers have found that women who have experienced sexual violence by a partner might suffer from PTSD (Bennice et al, 2003;Kessler et al, 2017;Zakrison et al, 2017;Honda et al, 2018), depression (Davhana-Maselesele et al, 2014;Honda et al, 2018), anxiety (Jaquier et al, 2015;Honda et al, 2018), substance and alcohol abuse (Decker et al, 2014;Jaquier et al, 2015;Hahm et al, 2017;Pengpid et al, 2018), somatic symptoms (Honda et al, 2018), sleep problems (Issahaku, 2015), and suicidal ideation and/or attempt (Sedziafa et al, 2016;Honda et al, 2018;Pengpid et al, 2018). They might also experience an unwanted pregnancy, abortion, being infected with HIV, and experience other forms of physical issues such as facial injuries, physical weakness, hypertension, and genital problems (Sedziafa et al, 2016).…”
Section: " I Had To Do That [What They Saw On Porn Clip] … I Didn't Hmentioning
confidence: 99%
“…Most research has focused on HIV vulnerability in the context of intimate partner violence (IPV); fewer studies have examined HIV risks from sexual violence perpetrated by any person, including nonpartners (García-Moreno, 2013). Finally, little is known about the sociodemographic, psychosocial, health, and clinical factors correlated with HIV acquisition through forced sex; this information can inform GBV prevention strategies and HIV care (Batchelder et al, 2016; Hahm, Augsberger, Feranil, Jang, & Tagerman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IPV has been linked with higher levels of sexual risk behaviors, including early onset sexual activity, forced unprotected sex, and increased substance use. 8 , 11 , 12 Studies have shown that abused women are more likely to have multiple sexual partners and less likely to use condoms, thus putting them at increased risk for STIs. 13 , 14 Furthermore, alcohol use before or during sex has been shown to be a potential risk factor of HIV/STI transmission and acquisition.…”
Section: Introductionmentioning
confidence: 99%